2011
DOI: 10.4028/www.scientific.net/amr.301-303.983
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Flame Height by Image Processing Method

Abstract: In order to measure the flame height (Lf), the image processing method was employed. The jet flame image was captured by the common-used digital camera. The resolution (C, with the unit of mm/pixel) of the pixel of the digital camera was calibrated by metric scale. The jet flame image was then successively processed by ROI (region of interest) processing, gray processing, binarization and edge detection. Through the image processing, the pixels where the flame root and the flame tip were located was detected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…It is demonstrated that estimating flame length and flame diameter accurately from images can be challenging and can result in large errors in the estimated HRR. Similar conclusions have been made by other authors [8]- [15]. There is clearly a need for a more robust method to estimate heat release rate, especially for outdoor fires.…”
Section: Appendix a Case Study Of Using Heskestad Equation To Predict...supporting
confidence: 86%
“…It is demonstrated that estimating flame length and flame diameter accurately from images can be challenging and can result in large errors in the estimated HRR. Similar conclusions have been made by other authors [8]- [15]. There is clearly a need for a more robust method to estimate heat release rate, especially for outdoor fires.…”
Section: Appendix a Case Study Of Using Heskestad Equation To Predict...supporting
confidence: 86%
“…Two procedures were used to determine the height of the flame. The first method is conducted by image processing analysis for flame image by a MATLAB code [6], [21], & [22]. Flame height is calculated by relating the flame pixel position with the burner pixels in the image.…”
Section: Procedures Of Flame Height Determinationmentioning
confidence: 99%
“…In industry, the flame height is particularly important since, for safety reasons and system integrity, the flame should not contact the combustion chamber walls in many applications. Flame height has been defined as is the distances of the burner tips to the point where the fuel appears in a stoichiometric condition with the oxidizers over flame centerline [6]. Hawthorne et al [7] presented the idea of a chemical flame height, which they described as "the length to the point where 99% full combustion appears".…”
Section: Introductionmentioning
confidence: 99%
“…The effects of different flame lengths and distances from the water mist nozzle to the burner tip on suppression time were examined. The flame length is measured using an image processing technique based on the intensity of flame similar to that presented by Zheng et al (Zheng et al 2011). Water was supplied to the nozzles at a pressure of 3.1 bar, generating droplet sizes in the range of 50-100 μm, according to Spray System Company manufacturer specifications.…”
Section: Interaction Of Water Mist With a Bunsen Burner Flamementioning
confidence: 99%